ANALISIS POTENSI PENCEMARAN LOGAM BERAT TIMBAL (Pb) PADA LINDI HIDROPONIK TANAMAN PAKCOY DENGAN METODE SPEKTROFOTOMETER SERAPAN ATOM - Azizah, Siti Halimatuz Zahroh; Alimuddin, Alimuddin; Widodo, Nanang Tri (PROSIDING SEMINAR KIMIA, 2024)
Analysis of the heavy metal lead (Pb) has been carried out in hydroponic leachate using nutrients (A-B mix) of pak-choy plants using the Atomic Absorption Spectrophotometer method. The samples used were 5 samples originating from 5 hydroponic installations at 2 different hydroponic cultivation locations. The research was carried out in the 2nd and 4th weeks of the hydroponic planting period. The sample preparation was wet destruction using HNO3. The research results showed that the levels of the heavy metal lead (Pb) in the 2nd week of testing, namely sample A was 0.9418 ppm: sample B was 0.9418 ppm; sample C was 2.2906 ppm; sample D was 2.2906 ppm and sample E was 6.3488 ppm. However, in the 4th week of testing no lead heavy metal contamination was found, the five samples used showed results <0.0016. So the results obtained are still below the quality standard value, namely a maximum of 5 ppm based on Minister of Agriculture Regulation No.261/KPTS/SR.310/M/4/2019. Keywords: Hydroponic leachate, Nutrition (A-B mix), Lead (Pb)